Analisis Proses Bisnis Gudang Logistik Halal Menggunakan Framework IDEF0: Studi Kasus Pada Cold Storage Halal - Wildan, Muhammad Izzatul; Bijaksana, Gena; Maulana, Andy (Jurnal Sistem Transportasi & Logistik, 2022)
This study aims to provide an overview of the background of the establishment of HLC, how the process of establishing HLC, and what the halal cold storage business process looks like. The object of this research is the halal cold storage business process. Analysis of the halal cold storage business process is carried out with a case study research design using the IDEF0 framework. The results show that: 1) The establishment of Halal Logistics & Cold Storage was previously MTI's effort to build a halal hub port as an accommodation for the halal logistics ecosystem in Indonesia. The previous managers wanted a facility that could accommodate halal logistics activities in Indonesia. Moreover, Indonesia is a country with the largest Muslim majority; 2) Then it was found that during the establishment of halal logistics, MTI conducted a study in Malaysia with a halal logistics consultant there to meet any halal logistics standards needed. MTI's efforts have also received support from the Indonesian Ulema Council with the existence of a joint memorandum of understanding on the preparation of a study on development cooperation and the operation of an integrated halal logistics area; 3) Whereas HLC has not fully played a role as logistics control in the halal supply chain because it does not yet have a halal supply chain network structure from supplier to consumer level, but HLC has business processes that have halal assurance value in the halal cold storage business processes owned.